2014
DOI: 10.1021/cs500466j
|View full text |Cite
|
Sign up to set email alerts
|

Active Sites in Sn-Beta for Glucose Isomerization to Fructose and Epimerization to Mannose

Abstract: Framework Lewis acidic tin sites in hydrophobic, pure-silica molecular sieves with the zeolite beta topology (Sn-Beta) have been reported previously to predominantly catalyze glucose−fructose isomerization via 1,2 intramolecular hydride shift in water and glucose−mannose epimerization via 1,2 intramolecular carbon shift in methanol. Here, we show that alkali-free Sn-Beta predominantly isomerizes glucose to fructose via 1,2 intramolecular hydride shift in both water and methanol. Increasing extents of postsynth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

32
380
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 266 publications
(416 citation statements)
references
References 27 publications
(79 reference statements)
32
380
3
1
Order By: Relevance
“…During our recent investigation of epimerization reactions of aldohexoses on alkaliexchanged Sn-Beta materials, a change in the reaction pathway from a 1,2-HS to a 1,2-CS upon alkali exchange was observed (11). This 1,2-CS pathway in aldohexoses is analogous to those previously reported for molybdate-and nickel(II) diamine-catalyzed reactions of these aldoses (also known as Bilik reaction), where simultaneous C-C bond-breaking and -forming steps were proposed to occur (SI Appendix, Scheme S1) (12,13).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During our recent investigation of epimerization reactions of aldohexoses on alkaliexchanged Sn-Beta materials, a change in the reaction pathway from a 1,2-HS to a 1,2-CS upon alkali exchange was observed (11). This 1,2-CS pathway in aldohexoses is analogous to those previously reported for molybdate-and nickel(II) diamine-catalyzed reactions of these aldoses (also known as Bilik reaction), where simultaneous C-C bond-breaking and -forming steps were proposed to occur (SI Appendix, Scheme S1) (12,13).…”
Section: Resultsmentioning
confidence: 99%
“…The recently reported increase in methyl lactate production by Sn-Beta from fructose in methanol at 170°C (from 16% to 57%) upon alkali carbonate addition (9) is consistent with formation of 1,2-CS sites upon alkali exchange of open sites in Sn-Beta. Sn-Beta systems with added borate and alkali salts were reported to be pH sensitive and are not efficient 1,2-CS catalysts in acidic conditions (11,30). Furthermore, if Sn-MFI is used as a size-dependent 1,2-HS catalyst in conjunction with borate-or alkali-modified Sn-Beta, borate or alkali ions have the capacity to enter the Sn-MFI pores and influence the efficiency of lactate production from trioses.…”
Section: Resultsmentioning
confidence: 99%
“…Later on, Bermejo-Devale tal. [76] reported experimental evidences upporting the conclusions of Rai et al [74] Bermejo-Deval et al have performed cationic exchange of H + of the silanol groupsf or Na + to excludet he possibility that the silanol groups participate in catalysis. Sn-b-containing silanol groups in the OH form (Sn-b)i somerize glucose into fructose ( Figure 8, left), whereas the catalysti nt he Na + form (Na-Sn-b)c atalyzes the epimerization of glucose into mannose (Figure 8, right).…”
Section: Isomerization Over Lewis Acidsmentioning
confidence: 88%
“…Such ab lockage of the open sites causesadramatic decreasei nt he catalytic activity,a nd this confirms the significance of the open sites for catalysis. [76] These tendencies are observedf or both water and methanol solvents. [76] Very recently,B rand et al have reported further evidencet os upport the fact that an adjacent silanolg roup participates in the hydride transfer mechanism.…”
Section: Isomerization Over Lewis Acidsmentioning
confidence: 91%
“…However, there is one possibility due to the absorbance of the CD 3 CN molecules adsorbed on the Brønsted acid sites through hydrogen bonding formed by the Sn ion doping. Thus, observed Brønsted acid sites might be due to the proton of the silanol group near the Sn atoms [38,39]. For example, Yang et al calculated the acid strength of the Brønsted acid sites in metal-doped MFI-silicates using density functional theory [40].…”
Section: Resultsmentioning
confidence: 99%